2014
DOI: 10.1007/s40259-014-0100-7
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Safety Evaluation of Trabectedin and Drug–Drug Interactions of Trabectedin-Based Combinations

Abstract: Trabectedin (Yondelis(®)) is a potent marine-derived antineoplastic drug with high activity against various soft tissue sarcoma (STS) subtypes as monotherapy, and in combination with pegylated liposomal doxorubicin (PLD) for the treatment of patients with relapsed platinum-sensitive ovarian cancer. This article reviews the safety and pharmacokinetic profiles of trabectedin. Records were identified using predefined search criteria using electronic databases (e.g. PubMed, Cochrane Library Database of Systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 85 publications
2
7
0
Order By: Relevance
“…Nevertheless, in a phase I trial posttreatment liver biopsies from eight patients treated with trabectedin/PLD showed no evidence of serious, unusual or persistent pathological liver abnormalities [4,14]. In accordance with the experience in several studies, liver enzyme elevation is usually reversible and non-cumulative and is not usually accompanied with a clinically relevant liver dysfunction [15].…”
Section: Hepatotoxicitysupporting
confidence: 75%
See 2 more Smart Citations
“…Nevertheless, in a phase I trial posttreatment liver biopsies from eight patients treated with trabectedin/PLD showed no evidence of serious, unusual or persistent pathological liver abnormalities [4,14]. In accordance with the experience in several studies, liver enzyme elevation is usually reversible and non-cumulative and is not usually accompanied with a clinically relevant liver dysfunction [15].…”
Section: Hepatotoxicitysupporting
confidence: 75%
“…The complete mechanism of action for trabectedin is complex and still not fully understood with anti-inflammatory effects within the tumor microenvironment are still under investigation [2]. Trabectedin is cleared mainly by hepatic metabolism involving the CYP3A4 system, therefore, co-administration of trabectedin with potent inhibitors of the enzyme CYP3A4 should be avoided and caution should be taken if medicinal products associated with hepatotoxicity are administered concomitantly with trabectedin, since the risk of hepatotoxicity may be increased [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, due to the sensitivity of CRC to anti‐angiogenic therapy, novel drugs killing TAMs, such as trabectedin, anti‐PD‐L1 antibodies, a pro‐apoptotic peptide M2 and PLX3397 (CSF‐1R tyrosine kinase inhibitor), might be evaluated in clinical trials as a new anti‐angiogenic strategy .…”
Section: Discussionmentioning
confidence: 99%
“…14 It is, however, well recognized that clinical outcome of cancer patients may differ whether they are treated in or out a clinical trial not only because of the higher heterogeneity of real-world patients, who often result unselected compared with those enrolled in investigational studies, but also because of the different background of each practice setting and the individual physician's experience/familiarity with therapeutic options and related toxicities. 15Y17 Therefore, despite the recommendations and guidelines, 11,18,19 variations in managing T/PLD administration in routine clinical practice across different centers/institutions cannot be excluded.…”
mentioning
confidence: 99%